1982
DOI: 10.1021/jm00347a014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biochemical properties of chemically stable product analogs of the reaction catalyzed by S-adenosyl-L-methionine decarboxylase

Abstract: Structural analogues of decarboxylated S-adenosyl-L-methionine (dc-SAM), product of the reaction catalyzed by S-adenosyl-L-methionine decarboxylase (SAM-DC), with modifications in the side-chain portion of the molecule have been synthesized, and their ability to inhibit SAM-DC has been investigated. Mainly, compounds with a nitrogen atom in place of the sulfur were investigated. The data from these inhibition studies have resulted in a delineation of the structural features required for binding on SAM-DC. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 8 publications
4
48
0
Order By: Relevance
“…Lower doses and longer-term randomized trials will be necessary to determine whether lower doses also produce these effects because the effect on tissue polyamines takes time and, except for one agent [topical trans-retinoic acid (69)], evaluation of chemoprevention agents in the Phase III setting has not borne out promising Phase II results in cervical intraepithelial neoplasia (70 -73). We have also measured the effect of 1 month of oral DFMO on polyamines in the prostate in patients undergoing a definitive surgical procedure, and we have demonstrated a marked lowering of polyamines; 6 (R. Love of Wisconsin has also obtained similar results. 7 ) Although DFMO has been highly effective as a chemoprevention agent in combination in preclinical models, to date only one clinical study has been reported using DFMO in combination (61).…”
Section: Clinical Studies Of Dfmo In Malignant and Precancerous Condimentioning
confidence: 76%
See 1 more Smart Citation
“…Lower doses and longer-term randomized trials will be necessary to determine whether lower doses also produce these effects because the effect on tissue polyamines takes time and, except for one agent [topical trans-retinoic acid (69)], evaluation of chemoprevention agents in the Phase III setting has not borne out promising Phase II results in cervical intraepithelial neoplasia (70 -73). We have also measured the effect of 1 month of oral DFMO on polyamines in the prostate in patients undergoing a definitive surgical procedure, and we have demonstrated a marked lowering of polyamines; 6 (R. Love of Wisconsin has also obtained similar results. 7 ) Although DFMO has been highly effective as a chemoprevention agent in combination in preclinical models, to date only one clinical study has been reported using DFMO in combination (61).…”
Section: Clinical Studies Of Dfmo In Malignant and Precancerous Condimentioning
confidence: 76%
“…The administration of DFMO to men who are scheduled for surgical interventions to treat some form of prostate hyperplasia or neoplasia causes a suppression in all prostate polyamine pools, including the spermine pool. 6 Supplying cells or animals with sufficient amounts of exogenous polyamines to restore normal intracellular pools can reverse most of the effects of DFMO (8,10,41). Several groups reported that polyamine metabolism was an integral component of the mechanism of carcinogenesis, especially in epithelial tissues.…”
Section: Effects Of Dfmo On Cell and Tissue Polyamine Contentsmentioning
confidence: 99%
“…More recently, the concept of 'multisubstrate adduct' inhibition has been successfully applied to the aminopropyltransferases [27]. Along these lines, S-methyl-5'-methylthioadenosine, a known inhibitor of AdoMet decarboxylase [13] and S-adenosyl-1,12-diamino-3-thio-9-azaadenosine have been shown to be potent inhibitors of spermine synthase both in vitro and in cultured cells [26,271. When used alone, these inhibitors cause marked decrease of sperrnine concentration in cultured mammalian cells and, therefore, are useful in the search for some specific biological functions of spermine.…”
Section: Discussionmentioning
confidence: 99%
“…A number of structural analogs of decarboxy AdoMet have been synthesized as potential inhibitors of AdoMet DC, and several of these have been shown to inhibit the enzyme from rat liver (16,20) and cultured L1210 cells (21) irreversibly. Two of these compounds were found to inhibit the growth of these cells in culture.…”
mentioning
confidence: 99%